Physical, Psychological, Social, and Environmental Quality of Life Among Elderly in Wetland Regions - Nur Yuliati; Ari Rahmat Aziz; Safri Safri (Jurnal Keperawatan Profesional, 2026)
Elderly people experience physiological, psychological, and social changes that can affect their quality of life. The condition of their living environment, including wetland areas, also has the potential to affect their well-being. This study aims to determine the quality of life of elderly people living in wetland areas. The study used a quantitative descriptive design with a sample of 264 respondents selected through a purposive sampling technique. Inclusion criteria included elderly people who were physically and mentally healthy, able to read and write, and willing to participate as respondents. The research instrument used the WHOQOL-BREF questionnaire, which assesses four domains of quality of life: physical health, psychological health, social relationships, and the environment. Data were analyzed univariately in the form of frequency distributions and percentages. The results showed that most respondents were aged 60–74 years (99.4%), female (78.8%), had an elementary school education or equivalent (59.5%), worked as housewives (73.9%), and were married (69.7%). In general, the quality of life of elderly people living in wetland areas was in the good category, with 198 people (75%). These findings indicate that older adults in wetland areas generally have a good quality of life and can serve as a basis for developing more responsive health programs and community services.